RETROSPECTIVE DIAGNOSIS OF PRIMARY IMMUNODEFICIENCIES FOR CHILDREN IN SVERDLOVSK REGION - S. S. Deryabina (SPb RAACI, 2016)
In order to justify a need for mass screening of primary immunodeficiencies (PID) in a regional program for the newborns, we performed a retrospective study of blood spots (archived screening cards) from the babies who deceased at the first year of life (n = 43). To this purpose, the copy numbers of T-cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC) have been measured. Notably decreased levels of TREC and (or) KREC were revealed in 16 cases (37.0%). Typical clinical pattern and presence of 22q11.2 deletion confirmed a PID diagnosis (DiGeorge syndrome) in one case. In five additional cases, the RAG1 gene defects have been detected, i.e., His249Arg (two heterozygous patients in our study), and Lys820Arg variants (one heterozygous case, and one compound heterozygote) have been observed in our group. Morover, one novel mutation was revealed in heterozygous state, i.e., c.1315C>G (Leu439Val). A synopsis of clinical patterns, hematological data, immunological testing and molecular biology could establish the PID diagnosis in these cases. Hence, we have confirmed a need for introduction of TREC and KREC determination in neonatal PID screening programs, aiming for their timely diagnostics and treatment.